Pink triangle legacies coming out in the shadow of the Holocaust - Newsome, W. Jake, 1987- (Cornell University Press, 2022)
"This book chronicles the seventy-five-year struggle for the acknowledgment and memorialization of the Nazis' LGBTQ victims. It simultaneously traces how LGBTQ people in Germany and the United States transformed the pink triangle from a Nazi concentration camp badge into an international symbol of queer identity and activism beginning in the 1970s"--